STATE BUDGET IN THE CONTEXT OF A WARTIME ECONOMY AND POST-WAR TRIGGERS FOR ITS RECOVERY - Serhii Petrukha; Dmytro Konovalenko; Nina Petrukha (Baltic Journal of Economic Studies)
The purpose of this study is to systematically analyse the functioning of the state budget of Ukraine in the context of the war economy and identify the key triggers of its post-war recovery. The article discusses the current challenges associated with the transformation of the structure of budget expenditures, a significant budget deficit, rising public debt and the need to attract international financial assistance. The wartime period for public finances is characterised by a significant shift in priorities, with the focus on security and defence forces, social support and the restoration of critical infrastructure. This reallocation of resources is a response to the unprecedented challenges faced by the state, but it creates additional risks to financial sustainability in the medium and long term, creating uncertainty about the triggers for post-war economic recovery from the consequences of the Russian-Ukrainian war. The main methods of the study are: quantitative analysis of economic and financial indicators of Ukraine and comparative analysis with other countries that have faced military conflicts. It is determined that the key barriers are the lack of domestic financial resources, high level of external debt and significant debt service costs. The impact of international financial assistance on ensuring macroeconomic stability and prospects for improving the efficiency of its use for resource support for economic recovery are also investigated. The qualitative analysis identified the main social and economic factors that influence the structure of the State Budget in the context of the Russian-Ukrainian war, including demographic changes, internal displacement of the population, the need to support veterans, and other previously unknown or insignificant factors that were inert in the pre-war period. Based on the results of the study, the author proposes a strategic context of triggers for the modernisation of public finances, including: further optimisation of the expenditure structure, improvement of the efficiency of budgetary resources management, introduction of innovative approaches to tax policy, and ensuring transparency in the use of international financial assistance. Particular attention is paid to the adaptation of international experience to Ukrainian realities, including the introduction of mechanisms for monitoring and evaluating the effectiveness of public spending. The practical significance of the study lies in the development of recommendations for improving the efficiency of public budget management in difficult economic conditions. It is determined that post-war reconstruction requires not only financial resources, but also the consolidation of efforts of the government, international partners and civil society. The main challenge is to strike a balance between the short-term needs to finance the security and defence forces and social protection and the long-term goals of sustainable development, which is becoming more inclusive. The authors propose an approach that combines rapid response to wartime challenges with laying the foundations for inclusive economic growth in the future. It is concluded that public finances are a key instrument for economic resilience during war and the basis for its post-war recovery. In particular, strategic management of budgetary resources will minimise the impact of external shocks, promote the development of domestic markets and ensure social stability. Further research in this area will contribute to the development of effective financial planning mechanisms adapted to Ukraine's current challenges and needs. It was also found that the war economy has significantly transformed the structure of Ukraine's state budget, directing major resources to defence and social support, which has led to unprecedented spending growth and budget deficits. At the same time, a sharp increase in public debt, including external debt, has highlighted the country's dependence on international assistance. In the post-war period, economic recovery will largely depend on investments in infrastructure reconstruction, which can become a driver of economic growth and job creation. Achieving financial sustainability requires comprehensive reforms of public financial management, effective use of international support, and stimulation of long-term economic development. In addition, the article emphasises the importance of promoting the use of the frozen assets of the aggressor country, which can become a source of financing for the restoration of Ukraine's infrastructure, helping to reduce the debt burden. The authors highlight the need for further research and integration of international experience in the field of financial stabilisation and development of an inclusive economy, which will help Ukraine to cope with the challenges of post-war recovery.